Bidirectional Power Converter Module (PCM) for Advanced Vehicle Electrification - S, Manasa; Bhaduri, Rupam (Journal of Power Electronics and Devices, 2023)
This research paper shows a Bidirectional Power converter Module (PCM) with an isolation transformer capable of performing diverse functionalities critical for vehicle electrification. The PCM is designed to enable Charging in systems involving grid-connected topologies for its regenerative capabilities, and bidirectional power flow functionality. This versatile converter is capable of giving various types of power outputs. Through modular configurations of PCMs, a wide range of voltage and power ratings can be achieved. The paper thoroughly elucidates the control algorithms for each operational mode, encompassing various grid functions. The simulation results aim to verify the performance of the converter. To attain high power density, the design incorporates SiC MOSFET power modules with high-frequency switching, complemented by an isolation transformer featuring a nanocrystalline core. In essence, this article presents a promising converter topology that provides many practical and relevant capabilities for the advancement of electric vehicles.